2023
DOI: 10.1021/acsapm.3c01308
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun Micro/Nanofiber-Based Biomechanical Sensors

Xiuhong Li,
Shuailong Zhang,
Kai Li
et al.

Abstract: Electrospun micro/nanofibers have gained popularity recently for flexible biomechanical sensors because of their advantages of lightness, compatibility, breathability, mechanical deformability, and function integrability, etc., offering them unprecedented sensitivities and versatilities. With increasing advances in the digital era, existing electrospun flexible sensors are not capable of catering to the demands of multiscenario applications including wearable electronics, interactive interfaces, and real-time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 216 publications
0
2
0
Order By: Relevance
“…Different forms of silver, whether nanoparticles or flakes, have conductivity 41,42 . For a silver‐filled conductive adhesive, the resistivity of the silver oxide and of the lubricant added are much higher than that of pure silver 43,44 . Because the added Ag + is not completely converted into Ag for the materials obtained in the dark, the charge transfer resistance R ct of the hydrogel obtained in the dark is smaller than for that obtained in the presence of light, and the conductivity increases, which indicates that Ag + and Ag 0 have a synergistic effect on the gel conductivity and also proves that Ag + is more conductive than Ag 0 in this gel.…”
Section: Resultsmentioning
confidence: 99%
“…Different forms of silver, whether nanoparticles or flakes, have conductivity 41,42 . For a silver‐filled conductive adhesive, the resistivity of the silver oxide and of the lubricant added are much higher than that of pure silver 43,44 . Because the added Ag + is not completely converted into Ag for the materials obtained in the dark, the charge transfer resistance R ct of the hydrogel obtained in the dark is smaller than for that obtained in the presence of light, and the conductivity increases, which indicates that Ag + and Ag 0 have a synergistic effect on the gel conductivity and also proves that Ag + is more conductive than Ag 0 in this gel.…”
Section: Resultsmentioning
confidence: 99%
“…While system parameters are viscosity, conductivity, and surface tension of the polymer solution, flow rate determination and applying electrical power to polymer blend are also processing parameters affecting the fiber diameter during fiber deposition onto the surface. Nanofibers are widely used in different areas, such as environmental engineering, biomedical engineering, tissue engineering, and mechanical engineering, due to high porosity, large surface area to volume ratio, good chemical and physical stability, and fast adsorption capabilities. Electrospun PAN-based nanofibers, such as PAN, polyacrylonitrile (PAN)/polypyrrole (PPy), the PAN/CA, are used for VOCs detection using the QCM method. Febrina et al showed that QCM-based PAN nanofiber sensors yielded a sensor response to various VOCs.…”
Section: Introductionmentioning
confidence: 99%